INVESTIGASI FUNDRAISING ZAKAT INFAQ SHADAQAH DI LEMBAGA AMIL ZAKAT INFAQ SHADAQAH NAHDLATUL ULAMA (LAZISNU) KABUPATEN PAMEKASAN - Achmad Jufri; Iqbal Rafiqi (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2020)
LAZISNU Pamekasan Regency as one of the amil zakat institutions which has quite high in 2018, which reached a total revenue of Rp. 1.5 Billion. Based on this, there are two focus studies in this research, namely: first, how to analyze the implementation of the Zakat Infaq Shadaqah (ZIS) fundraising strategy at the Amil Zakat Infaq Shadaqah Nahdlatul Ulama (LAZISNU) Institute of Pamekasan Regency; second, how to evaluate or control the fundraising strategy carried out by LAZISNU Pamekasan Regency. This study uses a qualitative approach with a descriptive type of research. Sources of data obtained through interviews, observation and documentation. The informants are supervisors, core management, and fundraising staff. While checking the validity of the data is done through persistence of observation and triangulation. The results showed that the implementation of the zakat infaq shadaqah fundraising strategy at LAZISNU Pamekasan Regency was carried out in collaboration with other organizations or agencies under the auspices of NU and institutions or companies. The first strategy that was prepared was to form a competent LAZISNU board. In the early stages, LAZISNU conducted mapping and data collection on prospective donors and muzakki (identification or segmentation and targeting) to determine the appropriate fundraising method. There are two methods used, namely direct fundraising and indirect fundraising. In addition, LAZISNU also provides special services for donors in the form of a donation pick-up service. Evaluation of the strategy or controlling fundraising zakat infaq shadaqah at LAZISNU Pamekasan Regency is held every month which is packaged with the column "lailatul ijitma'" to correct and improve strategy implementation so that it remains consistent in carrying out the fundraising strategy even though it is faced with internal and external problems.